A comparative study on the effect of carbon-based and ceramic additives on the properties of fiber reinforced polymer matrix composites for high temperature applications. Issue 24 (15th December 2021) - Ahmad, Shehryar; Ali, Sanan; Salman, Muhammad; Baluch, Abrar H.
Abstract: Ablative composites have been in use for thermal protection of space vehicles for decades. Carbon-phenolic composites have proven to perform exceptionally well in these applications. However with development in aerospace industry their performance needs improvement. In this field, different carbon-based and ceramic additives have been introduced into ablative composite systems. This review article gives a comparative analysis of researches done in this field in the recent past. Density, ablative, thermal and mechanical properties of ablative composites with different ultra-high temperature ceramic particles i.e. ZrSi2, Cenosphere, nano-SiO2, BN etc. and carbon-based nanoparticles i.e. CNTs, nano-Diamonds, Graphene oxide etc. used as additives, have been compared and discussed. Emphasis is put on carbon-phenolic composite systems although some epoxy matrix systems have also been discussed for comparison.